Faktor Risiko Stunting Balita pada Masa New Normal Covid-19 di Puskesmas Sukawati I Kabupaten Gianyar, Bali - Dina Indira Amrita Dewi; Luh Gede Pradnyawati; Anny Eka Pratiwi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[Risk Factors For Stunting In Toddlers At The New Normal Covid-19 Period At Puskesmas Sukawati I Gianyar District, Bali] Stunting is a growth problem due to lack of optimal nutrition. The world is facing the global COVID-19 pandemic affecting the increase in stunting cases because the fulfillment of basic and standard nutrition cannot be implemented during the pandemic. Because of this, eradicating stunting is one of the important agendas in the health sector in the era after the COVID-19 pandemic (new normal). The diagnosis of stunting is obtained if the Z-score of the length or height of the body to age is less than -2 SD (Standard Deviation) according to the World Health Organization (WHO) growth curve. The data for this study were obtained through direct clinical height measurements and filling out questionnaires. This study involved 60 children consisting of 30 children with stunting and 30 children without stunting. The results of the Chi-Square analysis showed that the low birth weight factor had a p-value of 0.002 which had a significant effect on stunting conditions with an OR value of 5,500 considered to be at greater risk of stunting (95% CI = 1,813 - 16,681), exclusive breastfeeding (p-value 0.003) had a significant effect on stunting with an OR value of 5,741 (95% CI = 1,724 - 18,994) considered to be at greater risk of stunting, feeding patterns (p-value 0.004) had a significant effect on stunting, an OR value of 4,929 (95% CI = 1,612 - 15,071) was considered to be at greater risk of stunting, utilization of health services (p-value 0.003) had a significant effect on stunting, an OR value of 5,231 (95% CI = 1,657 - 16,515) was considered to be at greater risk of stunting, and history of infectious diseases The value (P-value 0.002) has a significant effect on stunting with an OR value of 6,000 (95% CI = 1,890 - 19,043) is considered to be more at risk of stunting. So it is concluded that the risk factors for stunting during the new normal period of COVID-19 at the Sukawati 1 Health Center, Gianyar, Bali with a p value <0.05 which shows a significant relationship between exclusive breastfeeding factors, feeding patterns, utilization of health services, and history of infectious diseases with the incidence of stunting.